AC-driven, color- and brightness-tunable organic light-emitting diodes constructed from an electron only device - Zhao, Yongbiao (2016)
In this paper, a color- and brightness-tunable organic light-emitting diode (OLED) is reported. This OLED was realized by inserting a charge generation layer into an electron only device to form an n-i-p-i-n structure. It is shown that, by changing the polarity of applied voltage, only the p-i-n junction operated under positive bias can emit light and, by applying an AC voltage, emission from both junctions was realized. It is also shown that, by using a combination of blue- and red-emiting layers in two p-i-n junctions, both the color and brightness of the resulting white OLED can be tuned independently by changing the positive and negative amplitudes of the AC voltage.